Identification and Spatial Visualization of Dysregulated Bile Acid Metabolism in High-Fat Diet-Fed Mice by Mass Spectral Imaging - Zhang, Qi; Wu, Zhen-Hua; Zhao, Shan-Shan; Yang, Jing; Chen, Lei; Wang, Xiao-Yu; Wang, Zhan-You; Liu, Hui-Xin (Frontiers in Nutrition, 2022)
Changes in overall bile acid (BA) levels and specific BA metabolites involved in metabolic diseases, gastrointestinal and liver cancer. BAs have become established as important signaling molecules that enable fine-tuned inter-tissue communication within the enterohepatic circulation. The liver, BAs site of production, displayed physiological and functional zonal differences in the periportal zone versus centrilobular zone. In addition, BA metabolism shows regional differences in the intestinal tract. However, there is no available method to detect spatial distribution and molecular profiling of BAs within enterohepatic circulation. Herein, we demonstrated the application in mass spectrometry imaging (MSI) with high spatial resolution (3μm) plus mass accuracy MALDI to imaging BAs and N-1-naphthylphthalamic acid (NPA). Our results could clearly determine the zonation patterns and reginal differences characteristics of BAs on mouse liver, ileum and colon tissue sections, and the relative content of BAs based on NPA could also be ascertained. In conclusion, our method promoted the accessibility of spatial localization and quantitative study of BAs on gastrointestinal tissue sections, and demonstrated that MALDI-MSI was a valuable tool to investigate and locate several BAs molecules in different tissue types leading to a better understanding of the role of BAs behind the gastrointestinal diseases.